POSISI ILMU KEDOKTERAN DAN ILMU USHULUDDIN DALAM ILMU ISLAM - Danusiri, Danusiri (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2015)
As a lecturer, my job is to teach and to administer course of Islamic philosophy. However, the dynamics of the profession had once required me to serve as a lecturer in public colleges. In this institution, I teach Islamic subjects that are integrated with core content of every study program such as midwifery, nursing, nutrition, health analysts, public health, mathematics, statistics, and medicine. Through deep reflection I discovered the concept of 'basic philosophy of iqra', a term borrowed from Quraish Shihab, that derived from QS.Al-